Continuous versus intermittent beta-lactam infusion in severe sepsis: a meta-analysis of individual patient data from randomized trials - Roberts, Jason A.; Abdul Aziz, Mohd. Hafiz; Davis, Joshua S.; Dulhunty, Joel M.; Cotta, Menino O.; Myburgh, John; Bellomo, Rinaldo; Lipman, Jeffrey (American Thoracic Society, 2016)
Measurements and Main Results: We identified three randomized controlled trials in which researchers recruited a total of 632 patients with severe sepsis. The two groups were well balanced in terms of age, sex, and illness severity. The rates of hospital mortality and clinical cure for the continuous versus intermittent infusion groups were 19.6% versus 26.3% (relative risk, 0.74; 95% confidence interval, 0.56–1.00; P = 0.045) and 55.4% versus 46.3% (relative risk, 1.20; 95% confidence interval, 1.03–1.40; P = 0.021), respectively. In a multivariable model, intermittent β-lactam administration, higher Acute Physiology and Chronic Health Evaluation II score, use of renal replacement therapy, and infection by nonfermenting gram-negative bacilli were significantly associated with hospital mortality. Continuous β-lactam administration was not independently associated with clinical cure.